A study to investigate the effect of hormone replacement therapy (hrt) on platelet activation markers (cd62p & pac-1) in healthy postmenopausal women. - Ahmad Sheikh, Shabbir (2010)
Objectives: The aim of the study was to determine the effect of HRT on the platelet activation markers (CD62P & PAC-1) in healthy postmenopausal women. In such women platelet activation has been associated with the adverse cardiovascular events including unstable angina, myocardial infarction, stroke and other thrombotic states. There is much debate about the relationship between platelet function and serum estradiol levels including concerns about the influence of low estradiol in menopausal women. It is postulated that estrogen may result in decreased platelet activation. Methodology: A prospective case control study on 48 postmenopausal women was conducted at Hospital USM. Group-A consisted of 48 women NOT on HRT (Control Group) and Group-B comprised of same 48 women who were given HRT (Conjugated equine estrogen 0.625 mg orally once daily) for two weeks (Study group). Platelet activation was evaluated at baseline and after two weeks of treatment by flow cytometric analysis using CD62P and PAC1 as activation markers. Comparisons within groups (before and after HRT) were analyzed using the paired t-tests. Results: The expressions of CD62P and PAC1 showed a decreased platelet activation status in postmenopausal women who were given HRT. Platelet activation markers (CD62P & PAC-1) among healthy postmenopausal women in the group-A were 7.00% ±5.91 (CD62P) and 41.75% ±26.85(PAC-1) respectively (increased platelet activation in this group) which were reduced to 3.05% ±2.47 (CD62P) and 20.86% ±19.02 (PAC-1) respectively in the group-B after two weeks of HRT administration (p-value <0.001). Conclusion: HRT decreases the platelet activation markers (CD62P & PAC-1) in healthy post menopausal women. Platelet activation markers (CD62P & PAC-1) are found to be increased in healthy postmenopausal women as compared to the postmenopausal women who were treated with HRT. There is a significant negative fair correlation between estradiol and platelet activation markers (CD62P & PAC-1) however; there was no significant relation among BMI, age and platelet activation markers. It is concluded that short term use of HRT has a favorable effect on reduction of platelet activity in post-menopausal women and thus it is postulated to be cardio protective. Further study on the long term effect of HRT on platelets is needed.